Interactive Cohort Identification of Sleep Disorder Patients Using Natural Language Processing and i2b2 - Chen, W.; Kowatch, R.; Lin, S.; Splaingard, M.; Huang, Y. (Applied Clinical Informatics, 2015)
Nationwide Children’s Hospital established an i2b2 (Informatics for Integrating Biology & the Bedside) application for sleep disorder cohort identification. Discrete data were gleaned from semi-structured sleep study reports. The system showed to work more efficiently than the traditional manual chart review method, and it also enabled searching capabilities that were previously not possible.Objective: We report on the development and implementation of the sleep disorder i2b2 cohort identification system using natural language processing of semi-structured documents.Methods: We developed a natural language processing approach to automatically parse concepts and their values from semi-structured sleep study documents. Two parsers were developed: a regular expression parser for extracting numeric concepts and a NLP based tree parser for extracting textual concepts. Concepts were further organized into i2b2 ontologies based on document structures and in-domain knowledge.Results: 26,550 concepts were extracted with 99% being textual concepts. 1.01 million facts were extracted from sleep study documents such as demographic information, sleep study lab results, medications, procedures, diagnoses, among others. The average accuracy of terminology parsing was over 83% when comparing against those by experts. The system is capable of capturing both standard and non-standard terminologies. The time for cohort identification has been reduced significantly from a few weeks to a few seconds.Conclusion: Natural language processing was shown to be powerful for quickly converting large amount of semi-structured or unstructured clinical data into discrete concepts, which in combination of intuitive domain specific ontologies, allows fast and effective interactive cohort identification through the i2b2 platform for research and clinical use.Citation: Chen W, Kowatch R, Lin S, Splaingard M, Huang Y. Interactive cohort identification of sleep disorder patients using natural language processing and i2b2. Appl Clin Inf 2015; 6: 345–363http://dx.doi.org/10.4338/ACI-2014-11-RA-0106
Keywords: Sleep disorder; cohort identification; natural language processing (NLP); i2b2; clinical ontology